Users’ perception of hesitancy and delay in vaccination in Primary Health Care - Araújo Júnior, David Gomes; Meneses, Bruna Fontenele de; Aguiar, Jevanildo Paulino; Cardoso, Antônia Larissa de Miranda; Sales, Joaciara Nogueira de; Freire, Jordânia Marques de Oliveira (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Vaccination is an extremely important and necessary act from the beginning of a human being’s life. Aim: Unveil users’ perception of the reasons for hesitancy and delay in vaccination. Outlining: This is an exploratory-descriptive study with a qualitative approach, through the application of a semi-structured interview with users (51) of the Basic Health Units (UBS) in the city of Tianguá – CE, data collection was carried out between November and December 2021, the interviews were transcribed, Bardin’s content analysis technique (2016) was used to organize data and the results were presented with the help of the Iramuteq™ software. Results: four thematic categories were identified: 1 – Fear and dread of the adverse effects is a factor in the vaccine refusal, 2 – Challenges in ensuring user accessibility to vaccines, 3 – Users’ distrust about the benefits of vaccines and 4 – Lack of information and understanding about the effects of non-adherence to vaccination. It was then found that hesitancy and/or refusal to get vaccinated is motivated by multifactorial aspects, which can influence users’ decisions individually or jointly. Implications: Health professionals play a key role in promoting vaccination, being a preferred source of information indicated by users.